Tree carbon allocation explains forest drought‐kill and recovery patterns. (19th August 2018) - Trugman, A. T.; Detto, M.; Bartlett, M. K.; Medvigy, D.; Anderegg, W. R. L.; Schwalm, C.; Schaffer, B.; Pacala, S. W.
Abstract: The mechanisms governing tree drought mortality and recovery remain a subject of inquiry and active debate given their role in the terrestrial carbon cycle and their concomitant impact on climate change. Counter‐intuitively, many trees do not die during the drought itself. Indeed, observations globally have documented that trees often grow for several years after drought before mortality. A combination of meta‐analysis and tree physiological models demonstrate that optimal carbon allocation after drought explains observed patterns of delayed tree mortality and provides a predictive recovery framework. Specifically, post‐drought, trees attempt to repair water transport tissue and achieve positive carbon balance through regrowing drought‐damaged xylem. Furthermore, the number of years of xylem regrowth required to recover function increases with tree size, explaining why drought mortality increases with size. These results indicate that tree resilience to drought‐kill may increase in the future, provided that CO2 fertilisation facilitates more rapid xylem regrowth.